2017
DOI: 10.1371/journal.pone.0182588
|View full text |Cite
|
Sign up to set email alerts
|

HspB5 correlates with poor prognosis in colorectal cancer and prompts epithelial-mesenchymal transition through ERK signaling

Abstract: Alpha B-crystallin (HspB5) is abnormally expressed in tumor tissues and portends a poor prognosis in cancer patients. However, the role of HspB5 in colorectal cancer (CRC) is still unclear. Seventy CRC patients and 40 healthy volunteers were sampled from August 2012 to March 2015 in order to determine the clinical significance of HspB5. In vitro cellular studies were used to validate its molecular mechanisms in CRC. Our clinical data indicated that HspB5 was up-regulated, and had a positive association with TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 33 publications
(32 reference statements)
1
32
0
Order By: Relevance
“…Similar results were obtained by Li et al (2017) in a study conducted on 70 samples of colorectal cancer; they found up-regulation of αB-crystallin and its positive association with tumour stage and level of matrix metalloproteinase-7 (MMP-7). They also provided evidence that EMT induced by αB-crystallin may be regulated by ERK, PI3K and p38 signaling pathways [100].…”
Section: Annals Of Agricultural and Environmental Medicinesupporting
confidence: 83%
“…Similar results were obtained by Li et al (2017) in a study conducted on 70 samples of colorectal cancer; they found up-regulation of αB-crystallin and its positive association with tumour stage and level of matrix metalloproteinase-7 (MMP-7). They also provided evidence that EMT induced by αB-crystallin may be regulated by ERK, PI3K and p38 signaling pathways [100].…”
Section: Annals Of Agricultural and Environmental Medicinesupporting
confidence: 83%
“…These results indicate that inhibition of ANXA9 expression levels in HcT116 cells may induce suppression of AdMA17 and MMP-9 expression levels, but increase the TIMP-1 expression level contributing to the weakness of tumor cells in invasion and migration (26,32). Epithelial-mesenchymal transition (EMT) contributes to the invasion and migration of cRc (33). E-cadherin and N-cadherin are important in EMT of cRc (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] It is a member of small heat shock protein family and functions as a molecular chaperon in order to prevent the aggregation of proteins denatured by stresses, such as radiation and heat shock. 10 Recent studies have reported that increased expression of CRYAB renders several highly invasive and metastatic solid tumor cells, [13][14][15][16] whereas degradation and phosphorylation of CRYAB during enterovirus infection facilitates viral replication and induces viral pathogenesis. 17 Interestingly, several studies have reported that CRAYB plays protective and therapeutic roles in the development of neuroinflammation induced by injury, infection, neurodegeneration, and autoimmunity.…”
Section: Introductionmentioning
confidence: 99%